2022
DOI: 10.3390/cancers14040913
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Small Intestinal Neuroendocrine Tumors Metastasis: Biologic Patterns of a Series with Virchow’s Node Involvement

Abstract: Small intestinal neuroendocrine tumors (SI-NETs) may rarely metastasize to the left supraclavicular lymph nodes, also known as Virchow’s node metastasis (VM). Data on prevalence, prognostic significance, and clinical course of disease for SI-NET patients with VM is limited. In this retrospective analysis of 230 SI-NET patients treated at two tertiary referral centers, we found nine patients with VM (prevalence 3.9%). Among those, there were 5 females and median age at SI-NET and VM diagnosis was 61 and 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Endoscopic resection cannot be performed in such cases, and conventional surgery or adjuvant therapy can only be considered. The 5‐year OS and RFS of small bowel malignant tumors reported in previous studies after surgery and adjuvant treatment are much lower than our corresponding results 30,31 . A major reason for these differences may be that some of our patients had benign lesions or some of our patients had earlier tumor stages.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Endoscopic resection cannot be performed in such cases, and conventional surgery or adjuvant therapy can only be considered. The 5‐year OS and RFS of small bowel malignant tumors reported in previous studies after surgery and adjuvant treatment are much lower than our corresponding results 30,31 . A major reason for these differences may be that some of our patients had benign lesions or some of our patients had earlier tumor stages.…”
Section: Discussioncontrasting
confidence: 75%
“…The 5-year OS and RFS of small bowel malignant tumors reported in previous studies after surgery and adjuvant treatment are much lower than our corresponding results. 30,31 A major reason for these differences may be that some of our patients had benign lesions or some of our patients had earlier tumor stages. Limited data are available on ER of JILs, so such procedures' recurrence and overall survival rates are not well explored.…”
Section: Discussionmentioning
confidence: 93%
“…11 To date, comprehensive descriptive and survival analyses in patients with rare metastases are sparse. 3,7,8,13,20,24 Of note, earlier studies have reported significantly shorter OS for patients with bone metastases, as compared to patients with other types of distant metastases. 3,10 The prevalence of Virchow's lymph node metastasis among patients with abdominal and thoracic malignancies has previously been estimated to be up to 2.8%.…”
Section: Discussionmentioning
confidence: 95%
“…22,23 In two previous studies, the prevalence of Virchow's lymph node metastasis was 3%-4% in Si-NET and Pan-NET patients, but it was not associated with worse prognosis. 7,8 Finally, the presence of synchronous tumour deposits in both the small intestine and pancreas has been reported. In about one-third of the patients, two different primary tumours were identified according to the histopathological report after surgical resection.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation